Answer:
CD= 2x-1
Step-by-step explanation:
AD = 6x-4
AC = 4x - 3
CD= AD- AC
CD= 6x-4 - (4x - 3)
CD= 6x - 4 - 4x +3
CD= 2x -1
Therefore, the value of CD= 2x-1
They all have either a common factor, common multiple, LCF, GCF, LCM, or GCM. The G and L stand for greater and least.
Answer:16.110
Step-by-step explanation:
Answer:
![f(g(x))=\frac{1}{(x^{2}+1)^{2}} +\sqrt[3]{x^{2}+1}](https://tex.z-dn.net/?f=f%28g%28x%29%29%3D%5Cfrac%7B1%7D%7B%28x%5E%7B2%7D%2B1%29%5E%7B2%7D%7D%20%2B%5Csqrt%5B3%5D%7Bx%5E%7B2%7D%2B1%7D)
Step-by-step explanation:
we have
![f(x)=x^{2} +\frac{1}{\sqrt[3]{x}}](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E%7B2%7D%20%2B%5Cfrac%7B1%7D%7B%5Csqrt%5B3%5D%7Bx%7D%7D)

we know that
In the function

The variable of the function f is now the function g(x)
substitute
![f(g(x))=(\frac{1}{x^{2}+1})^{2} +\frac{1}{\sqrt[3]{(\frac{1}{x^{2}+1})}}](https://tex.z-dn.net/?f=f%28g%28x%29%29%3D%28%5Cfrac%7B1%7D%7Bx%5E%7B2%7D%2B1%7D%29%5E%7B2%7D%20%2B%5Cfrac%7B1%7D%7B%5Csqrt%5B3%5D%7B%28%5Cfrac%7B1%7D%7Bx%5E%7B2%7D%2B1%7D%29%7D%7D)
![f(g(x))=\frac{1}{(x^{2}+1)^{2}} +\sqrt[3]{x^{2}+1}](https://tex.z-dn.net/?f=f%28g%28x%29%29%3D%5Cfrac%7B1%7D%7B%28x%5E%7B2%7D%2B1%29%5E%7B2%7D%7D%20%2B%5Csqrt%5B3%5D%7Bx%5E%7B2%7D%2B1%7D)
Answer:
I would go with c.
Step-by-step explanation:
Hope this helped!